Peran Partai Politik dalam Formulasi Kebijakan Publik: Studi Kasus PDIP Kabupaten Kulonprogo Periode 2010-2012 - Istana, Istana; Suranto, Suranto (Journal of Governance and Public Policy, 2014)
The purpose of  this study was to describe the role of the  PDI-P in the formulation of  public policy in Kulon Progo2010-2012. This research method is qualitative research. Data collection techniques used were interviews and docu-mentation. Retrieval of  data from these sources is snowball, which is derived from selected informants that in theperspective of  researchers mengetahuiproses public policy formulation. Data analysis technique used is the tech-nique of  triangulation. The results of  this study of the PDI-P, Kulon Progo Regency has a strategic role for the welfareof  the people through various programs and building articulation of  community interests. Factors that affect the roleof  the PDI-P Kulon Progo is a factor in the formulation of a strong party leadership as well as the solidity of  the partyorganization. as the three pillars is a key player in the process of the emergence of public policy formulation. Each ofthese pillars has aspirations and authority, but in the unity of  responsibility.